Skatole (3-Methylindole) Is a Partial Aryl Hydrocarbon Receptor Agonist and Induces CYP1A1/2 and CYP1B1 Expression in Primary Human Hepatocytes - Rasmussen, Martin Krøyer; Balaguer, Patrick; Ekstrand, Bo; Daujat-Chavanieu, Martine; Gerbal-Chaloin, Sabine (PLOS ONE, 2016)
Skatole (3-methylindole) is a product of bacterial fermentation of tryptophan in the intestine. A significant amount of skatole can also be inhaled during cigarette smoking. Skatole is a pulmonary toxin that induces the expression of aryl hydrocarbon receptor (AhR) regulated genes, such as cytochrome P450 1A1 (CYP1A1), in human bronchial cells. The liver has a high metabolic capacity for skatole and is the first organ encountered by the absorbed skatole; however, the effect of skatole in the liver is unknown. Therefore, we investigated the impact of skatole on hepatic AhR activity and AhR-regulated gene expression. Using reporter gene assays, we showed that skatole activates AhR and that this is accompanied by an increase of CYP1A1, CYP1A2 and CYP1B1 expression in HepG2-C3 and primary human hepatocytes. Specific AhR antagonists and siRNA-mediated AhR silencing demonstrated that skatole-induced CYP1A1 expression is dependent on AhR activation. The effect of skatole was reduced by blocking intrinsic cytochrome P450 activity and indole-3-carbinole, a known skatole metabolite, was a more potent inducer than skatole. Finally, skatole could reduce TCDD-induced CYP1A1 expression, suggesting that skatole is a partial AhR agonist. In conclusion, our findings suggest that skatole and its metabolites affect liver homeostasis by modulating the AhR pathway.